Validity evaluation of the Health Information Preferences Questionnaire among college students - Tang, Kaiqi; Yuan, Junfeng; Luo, Lin (Frontiers in Public Health, 2024)
Objective This study aims to explore the association between health information preferences and specific health behaviors and outcomes, such as preventive measures and chronic disease management among college students. It assesses how different levels of health information preference influence individuals’ utilization, perception, and self-efficacy within healthcare and health information contexts. Given the rising prevalence of non-communicable chronic diseases among younger populations in China, this research seeks to understand how tailored health information preferences can support effective health education and behavioral interventions. The development of the Health Information Preference Questionnaire (HIPQ) aims to bridge the existing gap in tools for assessing health information preferences among Chinese college students, with a focus on collecting validity evidence to confirm the HIPQ’s applicability in this group. Methods The study employed a mixed-methods approach, beginning with an initial item pool derived from a comprehensive review of existing research tools, literature, and expert inputs. An expert review panel conducted item evaluations, leading to item reduction for clarity and relevance. The validation process utilized two independent samples of college students, detailing the sample size (n = 446 for preliminary testing, n = 1,593 for validation) and characteristics (age, major, urban vs. rural background) to enhance the understanding of the study’s generalizability. Results The HIPQ, comprising 25 items across five dimensions—prevention-oriented approaches, relationship with healthcare providers, self-efficacy in obtaining health information, perception of the importance of health information, and health information behavior—demonstrated excellent content validity (ICVI ranged from 0.72 to 0.86). Factor analysis confirmed significant loadings for each item across the anticipated factors, with fit indices (RMSEA = 0.065, CFI = 0.942) supporting good model fit. The HIPQ’s reliability was underscored by Cronbach’s alpha coefficients (>0.8) for each subscale, with significant correlations across all subscales, indicating strong internal consistency and construct validity. Conclusion The HIPQ proves to be a reliable and valid instrument for assessing health information preferences among Chinese college students, highlighting its potential for broader application in health education and intervention strategies. Recognizing the study’s focus on a specific demographic, future research should investigate the HIPQ’s adaptability and utility in broader populations and different cultural settings. The study’s limitations, including its concentrated demographic and context, invite further exploration into the HIPQ’s applicability across diverse groups. Additionally, potential future research directions could include longitudinal studies to assess the impact of tailored health information on actual health outcomes and behaviors.